2021
DOI: 10.1089/thy.2020.0393
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Normal Range Thyroid Function Affects Serum Cholesterol Levels, Blood Pressure, and Type 2 Diabetes Risk: A Mendelian Randomization Study

Abstract: Background: Observational studies have demonstrated that variation in normal range thyroid function is associated with major cardiovascular risk factors, including dyslipidemia, hypertension, type 2 diabetes (T2D), and obesity. As observational studies are prone to residual confounding, reverse causality, and selection bias, we used a Mendelian randomization (MR) approach to investigate whether these associations are causal or not. Methods: Two-sample MR analysis using data from the largest available genome-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 105 publications
(121 reference statements)
3
18
0
1
Order By: Relevance
“…Therefore, MR is an ideal method when we need to explore the causal relationship between different indicators. A recently published MR study analyzed the causality between thyroid function and cardiovascular risk factors such as blood pressure, blood lipids, diabetes, and obesity traits ( 49 ). The authors found no significant evidence of causal associations between genetically predicted TSH and BMI, or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MR is an ideal method when we need to explore the causal relationship between different indicators. A recently published MR study analyzed the causality between thyroid function and cardiovascular risk factors such as blood pressure, blood lipids, diabetes, and obesity traits ( 49 ). The authors found no significant evidence of causal associations between genetically predicted TSH and BMI, or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…A higher degree of ApoB-containing lipoprotein cholesterols is found in patients with TSH >10 mLU/L compared to those with TSH 4.0–10.0 mLU/L ( 17 , 18 , 19 ). Regardless of the thyroid status, circulating TSH level is always positively correlated with levels of ApoB-containing lipoprotein cholesterols ( 20 , 21 , 22 , 23 , 24 , 25 ). Hence the higher TSH level is, the greater the risks of dyslipidemia are ( 26 ).…”
Section: Dyslipidemia In Hypothyroidismmentioning
confidence: 99%
“…However, Bos and colleagues did find an association between genetic variants related to thyroid metabolism and insulin resistance ( 35 ), supporting a potential role of thyroid function in the pathogenesis of type 2 diabetes. A more recent mendelian randomization study by Kuś et al ( 36 ) found no association between thyroid hormones and type 2 diabetes in their main analyses, but when pleiotropic instruments were excluded, they observed that greater levels of TSH were statistically significantly associated with lower risk of type 2 diabetes. More research is needed to reconcile the differences between observational studies and mendelian randomization studies by exploring potential underlying mechanisms (eg, mediation analyses) and through an increase in genetic instruments for hypothyroidism and hyperthyroidism as well as TSH and FT4 (eg, larger explained genetic variability).…”
Section: Discussionmentioning
confidence: 88%
“…Two previous mendelian randomization studies have been performed with conflicting results ( 35 , 36 ). The first by Bos et al ( 35 ) found no association between TSH/FT4 with type 2 diabetes, suggesting that the association reported by traditional observational studies could be due to reverse causation or unmeasured confounding ( 35 ).…”
Section: Discussionmentioning
confidence: 99%